HLA y asma. - Ballester, José M.; Arce, Sergio; Buch, Abelardo; Ustariz, Catalino R.; Almaguer, Miguel; Fernández de Castro, J.; Rodríguez Gavaldá, Rubén; Enríquez, Gilda; Pérez, Sonia (Revista Cubana de Pediatría, 2023)
Sobre la asociación de antígeno HLA con enfermedades.